2022
DOI: 10.3390/met12020223
|View full text |Cite
|
Sign up to set email alerts
|

Predicting High Temperature Flow Stress of Nickel Alloy A230 Based on an Artificial Neural Network

Abstract: The high-temperature deformation behavior of metals and alloys undergoes complex mechanisms depending on the deformation conditions. The microstructure and mechanical properties after deformation are important factors that determine the strength and durability of the final product. Therefore, many studies to predict the microstructure and mechanical properties have been conducted. In this regard, numerous mathematical approaches for predicting microstructure and flow stress have been proposed over the past hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The typical BP ANN results for metal dynamic constitutive models are illustrated in the Figure 18, where the input layer typically includes temperature (T), strain rate ( . ε), and strain (ε), and the output layer represents the flow stress (σ) [129]. the training database and cannot replace the theoretical significance and research value traditional constitutive models [127].…”
Section: Artificial Neural Network Constitutive Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical BP ANN results for metal dynamic constitutive models are illustrated in the Figure 18, where the input layer typically includes temperature (T), strain rate ( . ε), and strain (ε), and the output layer represents the flow stress (σ) [129]. the training database and cannot replace the theoretical significance and research value traditional constitutive models [127].…”
Section: Artificial Neural Network Constitutive Modelmentioning
confidence: 99%
“…The output of its upper layer nodes is the input of the low layer nodes, including feedforward and backpropagation algorithms [128]. The typical ANN results for metal dynamic constitutive models are illustrated in the Figure 18, wh the input layer typically includes temperature (T), strain rate (𝜀𝜀), and strain (ε), and output layer represents the flow stress (σ) [129]. In 1995, Rao et al [130] applied the four-layer BP neural network to the flow str prediction of the thermal deformation process for the first time.…”
Section: Artificial Neural Network Constitutive Modelmentioning
confidence: 99%
“…Nevertheless, the accuracy of the models is highly dependent on the size and structure of the ANN. Moon et al [ 31 ] investigated the prediction accuracy of an ANN with different sizes, and they also revealed that the hidden layer size and node number have independent influences on the accuracy. Sani et al [ 32 ] predicted the constitutive equation of magnesium (Mg–Al–Ca) alloy by an ANN with one hidden layer and seven neurons per layer.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used constitutive models for prediction of flow stress are Arrhenius-type model [11][12][13][14][15], Johnson-Cook [16,17], Fields-Backofen [18][19][20][21], and Zerilli-Armstrong [22,23] models. In addition, models based on artificial neural network [24][25][26] and physical-based models [27][28][29] are also widely used. A brief review of most models is given in [30].…”
Section: Introductionmentioning
confidence: 99%